Controle da coleção em microfilme Relatórios ministeriais, BN/LAMP project, 1930-1960 ([publisher not identified], 1980)
Index to microfilm collection of "Relatórios" of various ministries of the Brazilian federal government from 1930 to 1960 filmed as part of a joint project of Plano Nacional de Microfilmagem de Periódicos Brasileiros, Fundação Nacional Pró-Memória, Biblioteca Nacional, and Latin American Microfilm Project.